PERAN OTORITAS JASA KEUANGAN DALAM PENERAPAN CUSTOMER DUE DILIGENCE PADA PEER-TO-PEER LENDING - Veronica, Angela; Murwadji, Tarsisius; Permana, Sudaryat (Mimbar Keadilan, 2022)
The innovation of P2P Lending that actualizes the Business-to-Business and Business-to-Consumer system has elevated economic productivity. P2P Lending offers a relatively fast and flexible money lending mechanism in which collateral is not mandatory as occurred in banking. However, the issue that arises in P2P Lending is the escalation of non-performing loan percentage that must be prevented through the implementation of effective risk mitigation by the Administrator of the Information Technology-Based Borrowing-Lending Services (Administrator). The research method used in this study is juridical-normative that utilizes the approach of laws, regulations and legal theory to analize the practice of P2P Lending within society. The results of this study indicate that Indonesia’s positive law has accommodated the risk mitigation procedures to reduce operational risk and credit risk, which are the root of the P2P Lending non-performing loan issue, namely through the implementation of CDD and EDD. OJK has a role to regulate and supervise such risk mitigation, especially to eradicate the emergence of unregistered and unlicensed Administrators by coordinating with SWI.